Aging and durability of concrete in lab and in field conditions – pore structure and moisture content gradients between inner and surface zones in RC structural elements. Issue 3 (4th May 2017) - Baroghel-Bouny, V.; Thiery, M.; Dierkens, M.; Wang, X.
Abstract : In real structures, gradients between inner and surface zones, which depend on the mix-design, as well as on curing and environmental conditions, are critical issues for durability, in particular when the mixture incorporates supplementary cementitious material (e.g. fly ash (FA)). This paper deals with pore structure and moisture content gradients, investigated not only on concrete samples in lab conditions, but also on reinforced concrete (RC) structural elements exposed for several years to three different outdoor environments (temperate climate, tidal zone in marine environment, as well as road and cold environment) and on full-scale structures (bridges). The experimental study was launched a lot of years ago within the framework of the large-scale and long-term "BHP 2000" French national project. The various mixtures studied (28-day cylinder compressive strengths ranging from 20 to 130 MPa) include high-performance concretes (HPCs) with or without silica fume (SF), as well as normal strength FA concretes. MIP pore size distributions obtained on the RC structural elements have been compared to lab results. In addition, in order to investigate the long-term drying(-wetting) behavior of the various types of materials studied here, water vapor desorption isotherms, internal relative humidity (RH), and degree of saturation profiles have been measured, respectively, by the saturated salt solution method, RH sensors, and gamma-ray attenuation on lab samples or on cores extracted from the elements and bridges at various times. The data have been analyzed as a function of the exposure conditions and of the mix-parameters. For example, the impact of early age external drying, carbonation, as well as freezing and thawing cycles in the presence of deicing salts has been highlighted on the field data. In addition, good performance of SF-HPCs and mature FA-concretes has been pointed out in the outdoor conditions considered.